Pascalia glauca poisoning in ruminants: Report of 12 outbreaks in northwestern Argentina. (30th July 2022) - Medina, Diego M.; Aguirre, Laura S.; Marin, Raul E.; Micheloud, Juan F.
Abstract: Pascalia glauca, a perennial herb known for its toxicity in ruminants, is one of the most important toxic plants in northwestern Argentina. This work describes several outbreaks of natural intoxication with P. glauca from different sources affecting cattle, sheep and goats in different production systems, with morbidity varying between 1% and 100%. Clinical signs included tremors in the hindquarters, recumbency and death. The liver showed swelling, congestion and a mottled appearance. Histopathologic findings included centrilobular hepatocellular necrosis with hemorrhage. Graphical abstract: Image 1 Highlights: Pascalia glauca causes acute liver failure in cattle, sheep and goats in Argentina. Centrilobular necrosis is the main liver lesion caused by P. glauca Animals are intoxicated by either direct grazing or ingestion of contaminated hay. Fresh P. glauca caused poisoning in cattle and sheep after the ingestion of single doses of 5–10 g/kg. Toxic doses for goats are probably higher than those for cattle and sheep.